Delivering co-stimulatory tumor necrosis factor receptor agonism for cancer immunotherapy: past, current and future perspectives - Dadas, Osman; Ertay, Ayse; Cragg, Mark S. (Frontiers in Immunology, 2023)
The tumor necrosis factor superfamily and their receptors (TNFRSF) are important regulators of the immune system, mediating proliferation, survival, differentiation, and function of immune cells. As a result, their targeting for immunotherapy is attractive, although to date, under-exploited. In this review we discuss the importance of co-stimulatory members of the TNFRSF in optimal immune response generation, the rationale behind targeting these receptors for immunotherapy, the success of targeting them in pre-clinical studies and the challenges in translating this success into the clinic. The efficacy and limitations of the currently available agents are discussed alongside the development of next generation immunostimulatory agents designed to overcome current issues, and capitalize on this receptor class to deliver potent, durable and safe drugs for patients.